The Good Friday oration ad intra ecclesiam in the context of the post-conciliar liturgical reforms - Dawid Mielnik (Warszawskie Studia Teologiczne)
This paper aims to juxtapose the differences between the versions of the Good Friday oration ad intra ecclesiam and unveil the theological character behind these modifications by analysing the prayers. The source materials were Benedict XV’s Roman Missal, Ordo Hebdomadae Sanctae Instauratus, Variationes in ordinem Hebdomadae Sanctae inducendae, and two typical editions of the reformed Roman Missals from 1970 and 2002. The paper is divided into three parts. In the first, the orations from the ad intra ecclesiam collection are explained. In the second, the changes to the orations are analysed. Finally, the influence on the theological character of the orations is presented. The analyses lead to the conclusion that it is difficult to specify a single criterion for the modifications in the ad intra ecclesiam collection. Sometimes, the changes resulted in a new organisation of the Church (e.g., oration for the Clergy and Laity of the Church), a shift in a person’s present state (oration for Those Preparing for Baptism), or a new understanding of the role of the Church in the world (oration for the Church). Some modifications are difficult to explain (oration for the Pope, for Those in Special Need).